Singing and femininity among the jalq'a and tarabuco (Bolivia) (Revista Argentina de Musicología, 2018)
Like other societies of the indigenous world, the jalq 'a and tarabuco from the Sucre region use their musical practices to define gender difference; to set the boundary between masculine and feminine. Thus, there is a gender distribution of the musical roles where men -except in some rituals- play the instruments and women sing. Although men al so sometimes join in the singing, the aesthetic ideal is in the women 's high pitched voices. A first glance al feminine vocal practices reveals that these are associated with the life cycle and divide it large stages. Through their singing. women move from a wild untamed time and space towards the socialized world of culture. a journey that, al the same time. plays an essential role in the elaboration of femininity.
Keywords: Andes; music; feminity; gender; voice